Long non-coding RNAs (lncRNAs); roles in tumorigenesis and potentials as biomarkers in cancer diagnosis - Najafi, Sajad; Khatami, Seyyed Hossein; Khorsand, Marjan; Jamali, Zeinab; Shabaninejad, Zahra; Moazamfard, Mostafa; Majidpoor, Jamal; Aghaei Zarch, Seyed Mohsen; Movahedpour, Ahmad (Experimental cell research, 2022)
New research has indicated that long non-coding RNAs (lncRNAs) play critical roles in a broad range of biological processes, including the pathogenesis of many complex human diseases, including cancer. The detailed regulation mechanisms of many lncRNAs in cancer initiation and progression have yet to be discovered, even though a few of lncRNAs’ functions in cancer have been characterized. In the present study, we summarize recent advances in the mechanisms and functions of lncRNAs in cancer. We focused on the roles of newly-identified lncRNAs as oncogenes and tumor suppressors, as well as the potential pathways these molecules could play. The paper also discusses their potential uses as biomarkers for the diagnosis and prognosis of cancer.